De toets. (Machelen-aan-de-Leie : Roger Raveelmuseum, 2007)
Devriendt, Robert ; Geyskens, Vincent ; Leroy, Eugène ; Mangold, Robert ; Prues, André ; Raveel, Roger ; Richter, Gerhard ; Van Severen, Dan
De toets, Roger Raveelmuseum, Machelen-aan-de-Leie, 3 december 2006 - 4 maart 2007
kunstcatalogus